Examining the Role of Legal Culture as a Protective Factor Against High Rates of Pre-trial Detention: the Case of Ireland - Rogan, Mary (European journal on criminal policy and research, 2022)
Ireland has a comparatively low pre-trial detention rate by European standards, at around 14 pre-trial detainees per 100,000 population. This article seeks to explore one factor which may explain a lower use of pre-trial detention in Ireland: its legal culture. Drawing on semi-structured interviews with judges, prosecution lawyers, defence lawyers and probation staff, the article finds that the constitutional protection of the right to bail (the key alternative to pre-trial detention in Ireland), an enduring legal tradition which historically prohibited the use of a risk of offending ground, and shared views and assumptions about the objectives of pre-trial detention hearings amongst judges, prosecution and defence lawyers, have influenced how such actors engage in the decision-making process about the use of pre-trial detention. The article argues that more attention needs to be given to the role of legal culture to examine why detention rates differ across Europe.